2019
DOI: 10.18178/ijiet.2019.9.12.1325
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Student’s Learning Achievement between the Flip Classroom with and without Group Management

Abstract: Abstract-Lecturers in universities normally use lectures as a primary teaching method. This teaching style has one drawback; it cannot respond to individual differences. A flipped classroom, on other hand, is an instructional strategy that allows students with different learning styles to learn together. It gives students a chance to study class materials, e.g., online lessons, videos and other appropriate media, as their suitable times and places in advance before the class. Then the students come in the cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The 362 FCM based studies involved different methodologies the analysis of which explored that the documents distributed on FLM in education, within the range of ten years (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020), mostly employed mixed-methods research design (f=178, %=49.17), followed by a quantitative research design (f=121, %=33.43). The analysis of research design revealed that multiple tools were utilized to collect in-depth information revealing the effectiveness of the FCM (e.g., Bouwmeester et al, 2019;Burns et al, 2019;Finkenberg & Trefzger, 2019;Halasa et al, 2019;Jitjumnong & Suksakulchai, 2019;Parra-Gonzalez et al, 2020;Wang & Zhu, 2019;Yang et al, 2019;Zamora-Polo et al, 2019). The tools utilized in gathering the required data were mainly surveys, questionnaires, observations, interviews and field notes.…”
Section: Methodsmentioning
confidence: 99%
“…The 362 FCM based studies involved different methodologies the analysis of which explored that the documents distributed on FLM in education, within the range of ten years (2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020), mostly employed mixed-methods research design (f=178, %=49.17), followed by a quantitative research design (f=121, %=33.43). The analysis of research design revealed that multiple tools were utilized to collect in-depth information revealing the effectiveness of the FCM (e.g., Bouwmeester et al, 2019;Burns et al, 2019;Finkenberg & Trefzger, 2019;Halasa et al, 2019;Jitjumnong & Suksakulchai, 2019;Parra-Gonzalez et al, 2020;Wang & Zhu, 2019;Yang et al, 2019;Zamora-Polo et al, 2019). The tools utilized in gathering the required data were mainly surveys, questionnaires, observations, interviews and field notes.…”
Section: Methodsmentioning
confidence: 99%
“…It is a way to manage long-term success based on performance, total participation, customer satisfaction, and benefits for all members of the organization and people. It was started by General Electric of the United States, and other industrialized nations have entered a new phase in the development of efficient management systems, including the implementation of sound management systems and improvements of their own qualities and characteristics [11]. Payant and Bell believe that total quality management refers to a quality management method for an organization to continuously improve product quality, mobilize all personnel to comprehensively use modern scientific management technology to conduct the whole process and comprehensive and systematic management of various factors affecting quality, and finally ensure that the products provided satisfy consumers [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kelas terbalik merupakan manajemen / mode pembelajaran yang memutarbalikkan kegiatan belajar tradisional yang menekankan pembelajaran teoretis dilakukan di ruang kelas menjadi dilaksanakan di rumah. Kegiatan belajar di rumah yang biasanya hanya untuk mengerjakan tugas tertentu diubah menjadi belajar materi dan mengerjakan penilaian (Bergmann & Sam, 2012;Lie, 2016) Jitjumnong and Suksakulchai, 2019). Selain mampu meningkatkan kemampuan belajar siswa, penggunaan mode kelas terbalik juga dapat mengembangkan kreativitas dan motivasi belajar siswa (Mubarok, 2017;dan Jiao, 2021).…”
Section: Pendahuluanunclassified